Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy: a clinicopathological and genetic study of a Swiss family. Issue 2 (August 1995) - Jung, H H; Bassetti, C; Tournier-Lasserve, E; Vahedi, K; Arnaboldi, M; Arifi, V B; Burgunder, J M
Abstract : This paper reports a Swiss family affected by a cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) linked to chromosome 19q12. In three generations several members of this family had recurrent stroke-like episodes and, some developed subcortical dementia, migraine-like headaches, and depression. The clinically affected family members had multiple subcortical infarcts and diffuse leukoencephalopathy on MRI. Necropsy of one patient showed a distinctive non-amyloid and non-atherosclerotic angiopathy of small cerebral and leptomeningeal arteries with concentric depositions of a basophilic granular material replacing the smooth muscle cells of the media. Linkage analysis with five chromosome 19 markers spanning the estimated CADASIL interval showed the absence of any recombinant and positive Lod scores, highly suggestive of linkage of this condition to the CADASIL locus. CADASIL might be an underestimated cause of familial stroke and should be considered in the differential diagnosis of hereditary stroke.